Effect of P2O5 content on the physical and biological properties of SiO2-Al2O3-CaO-Na2O bio-glass ceramics - Rahaman A.; Rahim A.; Pyare R. (My University, 2025)
Bio-active glass ceramics having a composition of 50SiO2-5Al2O3-23CaO [(22-X) Na2O-XP2O5[X= 3 and 6(weight %)] was prepared by melting method followed by sintering by powder processing route. The phase composition, surface morphology and structure of bio-glass ceramics were characterized. It has been found that the crystalinityof glass ceramics were increased by increasing the P2O5 content of the glasses. Protein adsorptions from human plasma (albumin) of these glass-ceramics were studied by UV spectrometer. It has been found that glasses and glass-ceramics having a higher amount of P2O5 adsorbed maximum protein and vice versa. © Research India Publications.